FAKTOR - FAKTOR KESULITAN BELAJAR PESERTA DIDIK PADA PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MTS NURUL MUJTAHIDIN MLARAK PONOROGO - Prahara, Erwin Yudi; Rochmawati, Marshella Putri Anggraini Noor; Hakiem, Ahmad Nu'man (Kodifikasia, 2023)
Basically the purpose of education is not only to shape students to be intelligent but also to shape individuals so that they have character or personality which can later grow and develop with a personality in which there are noble values and religion. Therefore, by incorporating religious values into subjects at school, it is hoped that it can create students with characters in which there are noble and religious values, one of which is through the subject of Islamic Cultural History (SKI). It is undeniable, for whatever we aim for, we will definitely encounter difficulties and challenges, as well as in the implementation of education based on Islamic values. This difficulty will later affect all aspects of student progress. For example, what happened to a school located in Ponorogo Regency, namely MTs Nurul Mujtahidin Mlarak, also experienced difficulties and challenges in delivering Islamic values-based learning, especially in the subject of Islamic Cultural History (SKI). Therefore, it is important to review further about the forms of difficulties, as well as what factors are likely to become obstacles in learning Islamic Cultural History (SKI), as well as solutions to deal with the various difficulties that have been mentioned. Pada dasarnya tujuan pendidikan tidak hanya membentuk siswa menjadi cerdas tetapi juga membentuk individu agar memiliki karakter atau kepribadian yang nantinya dapat tumbuh dan berkembang dengan kepribadian yang didalamnya terdapat nilai nilai luhur dan agama. Oleh karena itu dengan memasukkan nilai nilai keagamaan pada mata pelajaran di sekolah diharapkan dapat mewujudkan peserta didik dengan karakter yang didalamnya terdapat nilai nilai luhur dan agama, salah satunya melalui mata pelajaran Sejarah Kebudayaan Islam (SKI). Tak bisa dipungkiri, atas segala apapun yang kita tuju pasti menemukan kesulitan dan tantangannya tersendiri, begitu juga dalam penyelenggaraan pendidikan berbasis nilai Islam ini. Kesulitan ini nantinya akan mempengaruhi segala aspek kemajuan peserta didik. Seperti misalnya yang terjadi pada salah satu sekolah yang berlokasi di Kabupaten Ponorogo, yakni MTs Nurul Mujtahidin Mlarak, pun mengalami kesulitan dan tantangan dalam menyampaikan pembelajaran bebrbasis nilai Islam, khusunya pada mata pelajaran Sejarah Kebudayaan Islam (SKI). Oleh karenanya, penting untuk ditinjau lebih lanjut mengenai bentuk-bentuk kesulitan, serta factor-faktor factor-faktor apa saja yang memungkinkan untuk menjadi hambatan dalam pembelajaran Sejarah Kebudayaan Islam (SKI), serta bagaimana pula solusi untuk menghadapi berbagai kesulitan yang telah disebutkan.